Critical commentary: urban growth and access to opportunities: A challenge for Latin America from the ADC-Development Bank of Latin America / Comentário crítico: Crescimento urbano e acesso a oportunidades: um desafio para a América Latina do ADC - Banco de Desenvolvimento da América Latina - Rojas, Madisson Yojan Carmona; Oropeza, Oscar Adán Castillo (Revista de Direito da Cidade, 2020)
Abstract This essay discusses, based on a critical reading of the argumentative lines of the Urban growth and Access to opportunities: a challenge for Latin America Report. In the first place, the technical logics of the treatment of urban issues in Latin America, whose emphasis in quantitative variables ignores the socio-spatial contradictions derived from the existing intense class conflicts over the region. In the second place, it highlights that the discourse of development fostered by the ADC aims at generating efficient institutional arrangements, that is why the attention is directed to create “sustainable urban governance schemes” and not to generate political and economic strategies intended to unequal distribution of wealth in the region. In the third place, it is suggested in this comment, that under the protection of contemporary dynamics of capital, new instruments of public policies which promote financing the market of ground and housing are legitimized, while the need to integrate urban communities in the decision–making process is preached. Keywords: Bank of Development of Latin America, Urban growth, Socio-spatial contradictions, Class conflicts, Development, Metropolitan governance. Resumo Este ensaio discute, com base em uma leitura crítica das linhas argumentativas do crescimento urbano e acesso a oportunidades: um desafio para o Relatório da América Latina. Em primeiro lugar, a lógica técnica do tratamento de questões urbanas na América Latina, cuja ênfase nas variáveis quantitativas ignora as contradições socioespaciais derivadas dos intensos conflitos de classe existentes na região. Em segundo lugar, destaca que o discurso do desenvolvimento promovido pela ADC visa gerar arranjos institucionais eficientes, por isso a atenção é direcionada para criar “esquemas de governança urbana sustentável” e não para gerar estratégias políticas e econômicas destinadas à distribuição desigual de riqueza na região. Em terceiro lugar, sugere-se neste comentário que, sob a proteção da dinâmica contemporânea do capital, sejam legitimados novos instrumentos de políticas públicas que promovam o financiamento do mercado de solo e habitação, enquanto a necessidade de integrar as comunidades urbanas na decisão - processo de fabricação é pregado. Palavras-chave: Banco de Desenvolvimento da América Latina, Crescimento urbano, Contradições socioespaciais, Conflitos de classe, Desenvolvimento, Governança metropolitana.